Antara Kedaulatan Negara dan Kepastian Investor: Analisis Kritis Arbitrase Internasional dalam Sengketa Investasi Asing - Marcia Gladys Rumambi; Gunardi Lie (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the normative tension between state sovereignty and investor legal certainty within the framework of international investment arbitration. Employing a doctrinal legal approach, the research analyzes statutory regulations, international legal instruments, and arbitral jurisprudence to assess how legal norms structure the relationship between regulatory authority and investment protection. The findings indicate that arbitration does not eliminate state sovereignty but reconfigures it through legality, proportionality, and good faith standards. Legal certainty for investors is contingent upon compliance with domestic law, while states retain authority to regulate in pursuit of public interests. The study further demonstrates that inconsistencies in regulatory design and institutional capacity intensify disputes and undermine normative balance. Accordingly, a coherent legal framework integrating national legislation, contractual design, and international commitments is required to ensure equilibrium. The research contributes to doctrinal development by proposing a prescriptive model that aligns sovereignty with investor protection in a dynamic legal order while emphasizing the necessity of interpretative coherence, judicial consistency, and regulatory clarity in contemporary investment governance systems globally today.